Mediating role of authenticity in the relationship between destination image and destination loyalty - Yayuk Yuliana; Endang Sulistya Rini; Sirojuzilam; Syafrizal Helmi Situmorang; Amlys Syahputra Silalahi (Innovative Marketing, 2023)
Destination loyalty has become a topic that needs attention in tourism research, especially after the COVID-19 pandemic because it affects the number of visitors to tourist sites. This study aims to test the effect of destination image on destination loyalty through destination authenticity. The respondents in this study were visitors to the Ecotourism Mount Leuser National Park in Indonesia. The questionnaires were distributed to 301 respondents using purposive sampling. The data were processed using SEM-PLS methods. The results show that destination image influences destination authenticity (p-value <0.05). Next, destination authenticity affects destination loyalty (p-value <0.05) and destination image influences destination loyalty (p-value < 0.05). Finally, destination image through destination authenticity influences destination loyalty (p-value < 0.05). The findings of this study can be beneficial to the respective governmental bodies that seeks to improve destination authenticity and destination image to enhance destination loyalty of visitors and promote revisit intentions toward the Ecotourism Mount Leuser National Park in Indonesia. This study can be used as a reference for tourist destination managers to increase destination loyalty by maintaining and managing the tourist destination area properly. The government acts as a policymaker and is responsible for preserving the environmental impact of tourism, such as pollution, other environmental hazards, and land use issues stemming from poor planning, regulation, and engineering of the site, attractions, and facilities. AcknowledgmentThis study is funded by the DRTPM of the Ministry of Education, Culture, Research, and Technology, grant number [097/E5/PG.02.00.PT/2022], for the 2022 fiscal year.